Effect of High-speed Shearing Combined with Colloid on Blood Heat Aggregation Behavior of Frozen Ducks - Hao WANG; Zhongmin HUANG; Liqiang YAN; Mengmeng LEI; Huipin LI; Yanjie ZHANG; Zhili PAN (Shipin gongye ke-ji)
Frozen duck blood, as a new category of duck blood product other than duck blood tofu, enriched the types of duck blood products, but its quality was very different with the fresh duck blood. In this paper, the quality of frozen duck blood was effectively enhanced via ameliorating physicochemical properties and promoting the protein heat aggregation behavior of frozen duck blood. The influence of high-speed shearing combined with gellan gum (GG), carboxymethyl cellulose (CMC), gum arabic (GA), hydrolyzed collagen (HC), and sodium alginate (SA) on the thermal aggregation behavior of frozen duck blood was explored by this study through physical property analysis, nano particle size potentiometry, low-field nuclear magnetic resonance (LF-NMR), and scanning electron microscopy (SEM). The results showed that high-speed shearing combined with SA and HC exhibited better performance than that of CK, CMC, GA, and GG. The particle size increased from 704.34 μm to 1016.79 and 1018.86 μm. The absolute value of zeta potential increased from 12.58 mV to 21.23 and 23.55 mV, free sulfhydryl content decreased from 7.64 μmol/g to 4.78 and 4.33 μmol/g. Surface hydrophobicity index increased from 420 to 1270 and 1470. High-speed shear combined with sodium alginate or water-soluble collagen prompted the duck blood heat-induced gel molecules to form larger and more homogeneous protein aggregates, significantly enhancing the physicochemical properties. The hardness, elasticity and water retention of the gel were also drastically improved.